Forms of Subsistence from the Queer After the New Economic Crisis of 2020 in Cuba (Palimpsesto, 2022)
The study of the interrelationship between queerness, sex work and internal migration constitutes a subject little dusted off by the Cuban academy. The objective of this writing is to determine the forms of subsistence of trans migrant sex workers after the new economic crisis of 2020 in Cuba. The ethnographic method and the following techniques were used: participant observation, in-depth interviews and testimonies. What is queer is presented as a disobedience to order and new contact strategies such as Coronasutra and sexting are used.
Keywords: Internal migration; Livelihoods; Sex work; Queer; Cuba